The Factors Affecting Project Success Criteria – Aviation projects - AlQassem, Sohaib (2017)
Over few last years, there have been an enormous issues related to the construction projects especially when the cost and time overrun the estimated values. These issues are impacting all parties and projects stakeholder’s .As UAE and all developing countries are affected by such issues , the necessity of studying the factors affecting the project’s success criteria considered vital and the requirement to overcome these risks become important to all parties. In order to achieve this objective, a literature review has been conducted to provide a comprehensive understanding of the cost and time overrun risks and the factors affecting the project success criteria . In addition, the literature review shows the characteristic of airport projects and how it can be related to other construction projects. Furthermore , the best practices to mitigate the risks related to the project success criteria were reviewed and the difficulties encountered during the mitigation process were studied. This study conducted a quantitative analysis where a questionnaire was distributed to 60 professionals working in the aviation industry in UAE. The result of the survey shows the relationship between technical, organization capabilities and environmental factors with the project success criteria where it’s found that these factors have a significant impact on the project success criteria.